Utilitarian and spirituality of tatar style of living spaces - Gulnaz R. Akhmetshina, Klara H. Karamova, Iskander Z. Rauziev,; Usmanov, Salavat F. (Opción, 2019)
The study aims to investigate utilitarian and spirituality of Tatar style of living spaces in Kazan of late XIX - early XX century via historical and stylistic methods and comparative analysis of documents. As a result, the development of the Tatar residential architecture of Kazan took place mainly within the territorial frameworks of the Tatars’ living areas located beyond the Bulak Lake and the Upper Kaban. In conclusion, the importance of information about the utilitarian and spiritual nature of the Tatar style in the residential space of Kazan is enormous and priceless.